HUBUNGAN GAYA HIDUP DENGAN KEJADIAN HIPERTENSI PADA LANSIA : LITERATURE REVIEW - Awaluddin Awaluddin; Sharafinas Sharafinas (Jurnal Keperawatan Abdurrab, 2026)
WHO data indicates that there are 1.28 billion cases of hypertension worldwide. Hypertension can be controlled by maintaining a healthy lifestyle, including diet, obesity, and stress levels. The purpose of this literature review is to determine the relationship between lifestyle and hypertension. The method used in this paper is a literature review. A search for national and international journals was conducted using the Google Scholar database for the last five years, from 2020 to 2025. The search was conducted from November 2, 2024, to January 22, 2025. The keywords used in this literature review were elderly, lifestyle, hypertension, hypertension, lifestyle, and elderly. A total of 15,900 national journals and 44,300 international journals were found that matched these keywords. After evaluating the articles based on the criteria for the relationship between lifestyle and hypertension in the elderly, 20 national journals and 2 international journals met the criteria. Of these 22 journals, a p-value ranging from 0.00 to 0.044 was obtained, indicating a relationship between lifestyle and hypertension in the elderly.